Radioactive iodine uptake in hyperthyroid cats after administration of recombinant human thyroid stimulating hormone. (13th October 2018) - Oberstadt, Amy E.; Nelson, Nathan C.; Claude, Andrew K.; Refsal, Kent R.; Scott‐Moncrieff, J. Catharine; Petroff, Brian K.; Langlois, Daniel K.
Abstract : Background: Radioactive iodine therapy is considered the treatment of choice for hyperthyroidism in cats, but the availability of this modality is limited by costs and hospitalization requirements. Administration of recombinant human thyroid stimulating hormone (rh‐TSH) to humans with thyroid neoplasia or nodular goiter can increase thyroidal iodine uptake, thereby allowing the use of lower radioactive iodine doses for treatment. Veterinary studies of this subject are limited, and results are conflicting. Objective: To investigate the effects of rh‐TSH administration on thyroidal iodine uptake in hyperthyroid cats. Animals: Ten client‐owned hyperthyroid cats. Methods: In this prospective clinical study, cats were administered saline (placebo), 50 μg rh‐TSH (low‐dose), and 100 μg rh‐TSH (high‐dose) in randomized crossover design with treatments separated by 7‐10 days. After each treatment, thyroid scintigraphy was performed by administering 300 μCi 123 I and assessing radionuclide uptake 8 and 24 hours later. Serum thyroid hormone concentrations were measured at each visit. Results: Thyroidal percent iodine uptakes (mean ± SD at 8 and 24 hours) in cats treated with placebo (25.2 ± 13.4%, 30.0 ± 12.8%), low‐dose (24.1 ± 12.5%, 29.4 ± 13.7%), and high‐dose rh‐TSH (24.2 ± 16.3%, 30.8 ± 15.3%) were not different ( P = .76). Independent of rh‐TSH administration, percent iodine uptakes were positively correlated with serum thyroid hormone concentrations. Conclusions and Clinical Importance: One‐time administration of rh‐TSH, even at high doses, would not be expected to lower radioactive iodine doses needed for treatment of hyperthyroidism in cats. Investigations of alternate strategies to increase thyroidal uptake of radioactive iodine are warranted.